2021
DOI: 10.3390/foods10112851
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Excretion Study of Lycium barbarum Polysaccharides in Rats by FITC-Fluorescence Labeling

Abstract: A high-performance gel permeation chromatography fluorescence detection (HPGPC-FD) method combined with fluorescein isothiocyanate (FITC) labeling was established for the microanalysis of L. barbarum polysaccharides (LBP). The calibration curves linear over the range of 0.2–20 µg/mL in rat plasma, and 0.25–500 μg/mL in urine and feces samples with correlation coefficients greater than 0.99. The inter-day and intra-day precisions (RSD, %) of the method were under 15% with the relative recovery ranging from 84.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
3
9
0
Order By: Relevance
“…2E, both C max and AUC (0→∞) exhibited a positive correlation with the dose for each dose group, showcasing linear relationships of y = 0.8268x-8.5741 (R 2 = 0.9935) and y = 1.4153x + 24.585 (R 2 = 0.9531), respectively. This suggests that DPC1 demonstrates linear pharmacokinetic characteristics in mice, and similar dose-dependent outcomes were observed in the pharmacokinetic studies of other polysaccharides [25,31,38].…”
Section: Plasma Level Of Dpc1-rhbsupporting
confidence: 64%
See 1 more Smart Citation
“…2E, both C max and AUC (0→∞) exhibited a positive correlation with the dose for each dose group, showcasing linear relationships of y = 0.8268x-8.5741 (R 2 = 0.9935) and y = 1.4153x + 24.585 (R 2 = 0.9531), respectively. This suggests that DPC1 demonstrates linear pharmacokinetic characteristics in mice, and similar dose-dependent outcomes were observed in the pharmacokinetic studies of other polysaccharides [25,31,38].…”
Section: Plasma Level Of Dpc1-rhbsupporting
confidence: 64%
“…Pharmacokinetic experiments were conducted following the references [25,26]. Combined with the results of the pre-tests, the high, medium, and low doses were established for oral and intraperitoneal administration.…”
Section: Pharmacokinetics and Tissue Distribution Studiesmentioning
confidence: 99%
“…59,60 Moreover, recent work has pointed out that a small amount of LBPs with a low molecular weight of 4.9 kDa could enter the circulation and reach the liver. 61,62 It is widely accepted that one of the main organs where glucose uptake, gluconeogenesis and glycogen synthesis take place is the liver. 63 Therefore, to rule out the direct effects of circulating LBPs-4, further studies of pharmacokinetics and tissue distribution of LBPs-4 should be investigated.…”
Section: Food and Functionmentioning
confidence: 99%
“…Many reports have shown that polysaccharides can be absorbed into the intestine by oral or intragastric administration, and their effects can reach the kidneys [69][70][71]. Studies have shown that the concentration of polysaccharides in the kidney can reach 60 µg/mL or even higher in animal experiments [72].…”
Section: Upps Promote Crystal Endocytosismentioning
confidence: 99%